In light of the experience of the Bhils, what does it mean to be 'tribal'? (The South Asianist Journal, 2014)
This exploratory essay investigates constructions, perceptions and uses of the term 'tribal' in social and political discourse, drawing on current scholarship, and looking specifically at the case of the Bhils of Western and Central India. The essay looks briefly at the history of relations between the Bhils and neighbouring communities prior British colonial intervention, the changes introduced by British administrators seeking to 'clean' India's forests of their forest dwellers, and more contemporary issues associated with post-independence governmentality and minority entitlements, and the disputed rationales of privileging difference while simultaneously promoting integration.